Provenance Variation in Seed Parameters and Germination of Grewia optiva Drummond - Tyagi, P. C.; Agarwal, M. C.; Kumar, Nirmal (Indian Forester, 1999)
Statistical computation on seed traits and germination of the provenances revealed the existence of genetic variability. The correlation between different pairs of characters were determined and observed highly significant. The multiple regression equation using step-down regression techriique revealed that the seed length and lOO-seed weight might be used as the predictors of germination in Grewia optiva.